1984
DOI: 10.1002/anie.198404931
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins from Mold Fungi — Weapons of Uninivited Fellow‐Boarders of Man and Animal: Structures, Biological Activity, Biosynthesis, and Precautions

Abstract: In addition to the antibiotics, mycotoxins represent a second large group of biologically active substances of microbial origin. Over 300 mycotoxins are so far known and can be subdivided into 25 structural types. They are formed by approximately 350 molds of which there are 10000 different strains. As mycotoxin-producing molds tend to spread aggressively on foodstuffs, they can cause epidemic mycotoxicoses.-The mycotoxins have been isolated, their structures determined, and their biological activities investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 56 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…Despite the knowledge of the biosynthesis of several mycotoxins (Franck, 1984), the pathways and regulations for the biosynthesis of many mycotoxins are yet to be elucidated. The Environmental Protection Agency (EPA, 1997a) evaluated the safety of A. niger and concluded that ''mycotoxin production appears to be controlled by the conditions of fermentation'' and be strain specific.…”
Section: Conditional Production Of Toxic Metabolitesmentioning
confidence: 99%
“…Despite the knowledge of the biosynthesis of several mycotoxins (Franck, 1984), the pathways and regulations for the biosynthesis of many mycotoxins are yet to be elucidated. The Environmental Protection Agency (EPA, 1997a) evaluated the safety of A. niger and concluded that ''mycotoxin production appears to be controlled by the conditions of fermentation'' and be strain specific.…”
Section: Conditional Production Of Toxic Metabolitesmentioning
confidence: 99%
“…Malformins, produced from Aspergillus niger, are a group of cyclic pentapeptides with a disulfide bond formed from two cysteine thiols. The compounds express various biological activities, such as inducing root curvatures and malformations in plants, [1][2][3][4] antibacterial activity against Gram-positive and Gram-negative bacteria, [5][6][7] enhanced fibrinolytic activity 8 and inhibitory activity of the G 2 checkpoint. 9 Owing to their unique structures and diverse biological profiles, several processes for the synthesis of malformins have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the identification of mycotoxins responsible for mass intoxification of animals and humans was an epoch-making discovery in the last century (3). The epidemic Turkey "X" disease and the historical and modern cases of ergotism (St. Anthony's Fire) are infamous examples of mycotoxicoses, underscoring the global impact of food spoilage by fungi (3). Even low concentrations of mycotoxins in food can elicit deleterious effects such as chronic or acute toxic damage of liver and kidney.…”
mentioning
confidence: 99%